(untitled) (Annals of Medical Research, 2024)
Aim: Subepithelial lesions (SEL) of the gastrointestinal tract are lesions arising from the mucosa, submucosa or muscularis propria. This study is aimed to asses diagnostic characteristics of SELs on computerized tomography (CT) and to present the localization, size, CT attenuation and contrast enhancement patterns of the lesions that may aid in making correct diagnosis. Materials and Methods: Between December 2022 and March 2024, patients with a preliminary diagnosis of SEL on endoscopy or EUS and who underwent abdominal CT were retrospectively screened from the hospital database. Localization, size, pre-contrast and post-contrast Hounsfield Unit (HU) values of the lesions, and pathologic diagnoses were recorded and compared in patients with SEL. Results: Pathologic diagnosis was available in 25 (23.4%) patients with SEL detected on CT. Among these, the most common lesion was gastrointestinal stromal tumors (GIST, 52%). In 22 (20.6%) patients, the lesion was not detected on CT. The lesions that could not be seen on CT were less than 2 cm in size. Gastrointestinal distension was insufficient in the majority of patients in whom the lesion could not be visualized on CT. While the HU values increased by approximately 3 times in patients diagnosed with neuroendocrine tumors (median [interquartile ranges] 36.5 [32 – 40] vs. 101.5 [81.5 – 127.5]; p = 0.068), the increase was approximately 2 times in those with GIST (30 [29 – 38] vs. 70 [57 – 77]; p=0.003). Conclusion: This study presents several CT characteristics and pitfalls that may aid correct diagnosis of SELs with CT. SELs smaller than 2 cm in size and located in cardia are more likely to be missed with CT. Adequate gastric distention is crucial in correct diagnosis.